STRUCTURAL EQUATION MODEL (SEM) METHOD IN ANALYZING FACTORS AFFECTING STUDENT ACHIEVEMENT FROM CAMPUS ENVIRONMENT CHARACTERISTICS - Trisna Islamia; Pasukat Sembiring (MES: Journal of Mathematics Education and Science, 2022)
Achievement of student academic achievement is influenced by various factors both inner factor of student (internal factor) and factor from outside student self (external factor). One of the external factors affecting student achievement is the campus environment. This study aims to obtain the best structural equation model which can describe the relationship between latent variables, the relationship between the latent variables and the indicator variables, to find out which one is the most influencing and to know which construct most influence the achievement of the three indicators, namely motivation, attitude toward almamater, attitude towards lecturer. In this paper, SEM is used to determine student achievement model of Mathematics S1 FMIPA USU. Structural Equation Modeling (SEM) is a multivariate analysis that aims to simplify complex independent variables into simpler and easier to understand forms. The research material is the result of mathematics student survey of FMIPA USU stambuk 2013,2014,2015 by using questionnaire measured by likert scale and using simple random sampling technique. The results of data analysis obtained parameters as follows: achievement with attitude toward alamamater 0,084, achievement with attitude toward lecturer 0,267, achievement with motivation 0,01.